The contribution of legal medicine in clinical risk management - Matteo Bolcato; Giacomo Fassina; Daniele Rodriguez; Marianna Russo; Anna Aprile (BMC, 2019)
Abstract Background In advanced health services, a main objective is to promote the culture of safety and clinical risk management. In this regard, the reporting of sentinel events fits within a perspective of error analysis, attempting to propose solutions aimed at preventing a new occurrence of the harmful event. The purpose of this study is to analyze the contribution of medico-legal litigation in the management of clinical risk and to propose an organizational model so as to coordinate the intervention of clinical risk management and medico-legal services. Methods Retrospective review of 206 cases of medico-legal litigation, settled against a Hospital of a North-eastern city in Italy from January 1, 2014 and December 31, 2015. Results Approximately 20% of cases, that are classifiable as "sentinel events", were not reported due to various factors. The reason that these events are under-reported is mainly due to the latency between the event itself and its manifestation as a serious damage to health as well as the discomfort in reporting the events of this kind, which is still widespread among healthcare workers. The systematic research of the available documentation for medico-legal purposes permits the acquisition of more information concerning the clinical event, thereby increasing the number and accuracy of the reports to the clinical risk unit. Conclusion The analysis of medico-legal litigation is a valid tool to enhance the reporting of "sentinel events". One possible proposal is the implementation of an organizational model to establish a rapid procedure for the reporting of sentinel events during the evaluation of medico-legal litigations.